2016
DOI: 10.1097/mib.0000000000000769
|View full text |Cite
|
Sign up to set email alerts
|

Serum Infliximab, Antidrug Antibodies, and Tumor Necrosis Factor Predict Sustained Response in Pediatric Crohnʼs Disease

Abstract: ATI, s-IFX, and s-TNF-α during IFX induction are associated with 12-month clinical outcomes in pediatric CD. Future studies are needed to further define the clinical role of s-TNF-α measurement and to compare the clinical utility of 10 and 14-week ATI and s-IFX levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
1
34
2
Order By: Relevance
“…In contrast to tissue TNF‐α, serum TNF‐α is convenient to measure and can be performed on the same samples used to measure the serum anti‐TNF‐α agent levels. Stein et al . recently published an investigation of serum IFX, anti‐IFX antibody, and serum TNF‐α in pediatric patients with CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to tissue TNF‐α, serum TNF‐α is convenient to measure and can be performed on the same samples used to measure the serum anti‐TNF‐α agent levels. Stein et al . recently published an investigation of serum IFX, anti‐IFX antibody, and serum TNF‐α in pediatric patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In contrast to tissue TNF-α, serum TNF-α is convenient to measure and can be performed on the same samples used to measure the serum anti-TNF-α agent levels. Stein et al 34 recently published an investigation of serum IFX, anti-IFX antibody, and serum TNF-α in pediatric patients with CD. They demonstrated that a decrease in serum TNF-α levels from baseline is a predictive factor for continuing IFX therapy at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…112 In pediatric Crohn's disease, higher concentrations of infliximab during the induction phase predict a sustained response to the drug. 113 Combination therapy: immunomodulators and anti-TNF Immunomodulators such as azathioprine/6-mercaptopurine and methotrexate have recently been used in an attempt to restore response to an anti-TNF agent once the patient has developed antibodies against the drug (n=5, young adults). 114 In a retrospective review of the PIBD Collaborative Research Group Registry, infliximab plus an immunomodulator was found to increase the chance that the patient would benefit from infliximab for five years (n=502).…”
Section: Biologicsmentioning
confidence: 99%
“…The value of albumin, haemoglobin and CRP for predicting anti‐TNF response has been reported in several studies (Table S7). Evidence from one study suggests that baseline neutrophil‐to‐lymphocyte ratio predicts secondary loss of response to IFX treatment in UC patients (HR 3.86 [1.20‐12.4], P = 0.023; AUC 0.798) …”
Section: Resultsmentioning
confidence: 99%